ADMINISTRATOR’S ROLE IN PERFORMANCE BASED REWARD AS A DETERMINANT OF EMPLOYEE OUTCOMES - Azman ISMAIL; Mohammad Fuad ZAIDI; Aimi ANUAR (Management & Marketing)
According to the recent literature pertaining on workplace compensation program, administrators often play two important roles in planning and implementing performance based reward: communication and performance appraisal. Recent studies in this field highlights that the ability of administrators to appropriately communicate pay information and appraise employee performance may have a significant impact on employee outcomes, especially job satisfaction and organizational commitment. Therefore, this study was conducted to assess the relationship between administrator’s role in performance based reward and employee outcomes using self-administered questionnaires collected from employees at a district council in Malaysia. The outcomes of the SmartPLS path model analysis showed that pay communication does not act as an important determinant of job satisfaction, but performance appraisal does act as an important determinant of job satisfaction. Conversely, both pay communication and performance appraisal act as important determinants of organizational commitment. Hence, discussion, implications and conclusion are elaborated.